Distribution and Condition of Hard Coral (Scleractinian) Species in the Waters of Airlouw and Seri Village - S. R., Loupatty,; G. V., Limmon,; S. M. J., Kaya,; G. D., Manuputty. (Agrikan Jurnal Agribisnis Perikanan, 2023)
The waters of Air Louw and Seri Village are located in the southern part of Ambon Island and are classified as high in human activity due to their high biodiversity. In Airlouw waters, beach and marine tourism activities are part of the life of the local community, while Seri waters tend to be high in fishing activity. This condition can lead to the degradation of coral reef ecosystems, and we need a good database on the types of corals, their distribution, and the conditions of coral reef ecosystems. Data was collected by combining the Line Intercept Transect (LIT) and Photo Transect methods and carried out at 3 and 10 meters deep. The distribution of hard coral species at the two study sites resulted in 87 species of hard coral (Scleractinia) from 27 genera, 12 families. Fifty-seven scleractinian species were found at the intersection of the transect lines and 30 other species around the transect lines. In general, the condition of coral reefs at Airlouw station is classified as Medium (28. 25%), with the dominant growth forms at a depth of 3 m and 10 m being Acropora Branching and Coral Encrusting. At the Seri station, the condition of coral reefs is also categorized as moderate, namely 38. 25%, with the dominant growth forms, namely Coral Massive and Coral Branching. The condition of the coral reefs in both locations needs attention to manage the ecosystem further.